Motivasi Wisatawan Millenial Memilih Kuliner Lokal Sebagai Daya Tarik Wisata Di Ubud Kabupaten Gianyar Bali - Ariani, Ni Made; Setiawan, Ida Bagus Dwi (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2023)
Ubud as the center of tourism activities in Gianyar district, you can easily find various types of tourist attractions and tourism supporting facilities. one of them is a restaurant. Ubud was named one of the best cities in Asia by Conde Nast Traveler in 2013, at that time Ubud achieved the highest score based on indicators of atmosphere, art and culture, lodging, restaurants, sites, people's friendliness, and shopping facilities. One of the components that support Ubud in winning the award is the restaurant criteria. Based on the study above, the authors are interested in studying the motivation and determinants of millennial tourist motivation for local culinary tours in Ubud. Data collection used a questionnaire with a scale of 5. The number of samples was determined by quota sampling with predetermined respondents being searched accidently. Data analysis technique using confirmatory factor analysis. Based on the results of the study it was concluded that the motivation of millennial tourists in choosing local culinary as an attraction in Ubud is mostly driven by emotional motivation where purchases made by consumers are based on feelings and pleasures that can be captured by the five senses, and if this is done it will increase status their social. This is reflected in the answers of respondents who feel proud when they enjoy the culinary dishes offered in Ubud and feel happy with these culinary dishes. The motivating factors that determine millennial in choosing local culinary as a tourist attraction in Ubud, Gianyar Regency are factor 1 is the convenience and practicality factor, factor 2 is service, factor 3 is product and factor 4 is location and price. The four factors that determine millennial motivation in choosing local culinary offerings in Ubud, Gianyar Regency, have an influence of 65.64%. Keywords: Local Culinary, Motivation, Restaurants, Culinary Tourism, Millennial Travelers